PERANCANGAN ALAT TIDUR UNTUK MENINGKATKAN KUALITAS TIDUR STUDI KASUS MAHASISWA UNIVERITAS TELKOM PROGRAM STUDI DESAIN PRODUK - Huda, Dzikra Rahmah Nurul; Pambudi, Terbit Setya; Yunidar, Dandi (Telkom University, 2024)
Students as one of the roles in the academic community globally have poor sleep quality, which affects their academic performance and overall quality of life. Students themselves Students themselves have a tendency to be able to fall asleep more easily comfortably when they hug something, sleeping equipment products are designed by considering ergonomic shapes to avoid the onset of aches or pains during sleep and when waking up, as well as cool materials. This problem is the basis for designing a sleeping device to improve sleep quality for students with an ergonomic and anthropometric approach, designed using the User-Centered Design (UCD) method to make students the main users of the product as well as the main source of data for research and design. Keywords: Sleep quality, student, UCD, ergonomic-anthropometric sleep tool.